The Impact of Enhanced Recovery after Surgery Protocol Implementation on Postoperative Pain Management in the Era of Opioid Crisis: The Postchemotherapy Open RPLND Experience - Dimitropoulos, Konstantinos; Pisters, Louis L.; Papandreou, Christos N.; Daliani, Danai; Karatzas, Anastasios; Petsiti, Argiro; Tassoudis, Vassilios; Arnaoutoglou, Eleni; Vlachostergios, Panagiotis J.; Tzortzis, Vassilios (Current Cancer Drug Targets, 2023)
Aim: Enhanced Recovery After Surgery (ERAS) protocols have been proven to optimize postoperative outcomes; however, misuse of opioid analgesics can still hinder postoperative recovery due to related side effects and potential complications. Introduction: To determine if the implementation of ERAS protocol in post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND) patients could help with reducing postoperative pain and opioid use. Methods: A case-control study of consecutive testicular cancer patients with indications for PCRLPND, who were offered Conventional Post-operative Management (CPM) or ERAS protocol. Outcomes of interest included Visual Analogue Scale (VAS)-assessed pain level at postoperative days 3, 7, and 30, and Morphine-Equivalent Doses (MEDs)/postoperative day. Intraoperative parameters and postoperative complications were recorded. Parametric and non-parametric tests were used for statistical analysis. Results: In total, 100 opioid-naïve PC-RPLND patients were studied. CPM and ERAS groups (36 and 64 patients, respectively) had similar demographic and baseline clinical characteristics). ERAS group patients had significantly lower blood loss (p = 0.005), blood transfusion rate (p < 0.001), and duration of the procedure (p < 0.001). Post-operative complications were comparable between groups. Nausea and bowel disorders were numerically but not statistically more frequent in the CPM group. ERAS patients had shorter mean hospital stay (5.3 ± 1.4 vs. 7.4 ± 1.6 days, p < 0.001), lower daily MEDs (4.73 ± 2.63 vs. 7.04 ± 2.29, p < 0.001), and lower VAS scores on post-operative day 7 (3.89 ± 1.07 vs. 4.67 ± 1.17, p = 0.001). Post-operative pain was similar between groups on post-operative days 3 and 30. Conclusion: Systematic implementation of ERAS protocol after PC-RPLND improves pain management, optimizes patient recovery, and prevents over-prescription of opioid analgesics.
Keywords: RPLND